Non-UV germicidal activity of fresh TiO(2) and Ag/TiO(2) - LIU, Lifen (J Environ Sci (China), 2009)
Fresh TiO(2) was found to possess a strong germicidal activity even without UV irradiation. Live Yeast (Saccharomyces cerevisiae) cells in contact with fresh TiO(2) were found deformed and dead after 15 min contact. The cause of germicidal activity was discussed from the observed cell deformation, lysis and increased absorption at 1680 cm(−1) in FT-IR spectra of the affected cells, which proved the oxidizing effect of fresh TiO(2) to cells. The deformation caused by the stretching of cell wall and pressure built-up inside the cell, led to cell burst and release of intracellular materials. The degree of cell deformation was found positively related with the wetting property of TiO(2). Cells are negatively charged, for Gram-negative cell (thinner cell wall), a higher germicidal effect was observed than Gram-positive cells. The germicidal effect of TiO(2) gradually decreased after exposure to air at room temperature, as the wetting property decreased. This kind of germicidal activity was more effective compared to other germicidal process such as UVA/TiO(2) or Ag(+). This shed light on designing new germicidal material either maintained by visible light irradiation, or by oxidation effect generated by reactive oxygen species.